Electroosmotic Flow in Nanofluidic Channels - Haywood, Daniel G. (Anal Chem, 2014)
[Image: see text] We report the measurement of electroosmotic mobilities in nanofluidic channels with rectangular cross sections and compare our results with theory. Nanofluidic channels were milled directly into borosilicate glass between two closely spaced microchannels with a focused ion beam instrument, and the nanochannels had half-depths (h) of 27, 54, and 108 nm and the same half-width of 265 nm. We measured electroosmotic mobilities in NaCl solutions from 0.1 to 500 mM that have Debye lengths (κ(–1)) from 30 to 0.4 nm, respectively. The experimental electroosmotic mobilities compare quantitatively to mobilities calculated from a nonlinear solution of the Poisson–Boltzmann equation for channels with a parallel-plate geometry. For the calculations, ζ-potentials measured in a microchannel with a half-depth of 2.5 μm are used and range from −6 to −73 mV for 500 to 0.1 mM NaCl, respectively. For κh > 50, the Smoluchowski equation accurately predicts electroosmotic mobilities in the nanochannels. However, for κh < 10, the electrical double layer extends into the nanochannels, and due to confinement within the channels, the average electroosmotic mobilities decrease. At κh ≈ 4, the electroosmotic mobilities in the 27, 54, and 108 nm channels exhibit maxima, and at 0.1 mM NaCl, the electroosmotic mobility in the 27 nm channel (κh = 1) is 5-fold lower than the electroosmotic mobility in the 2.5 μm channel (κh = 100).